Pheromone Blend Variation and Cross-Attraction among Populations of the Black Cutworm Moth (Lepidoptera: Noctuidae). (1st November 2014) - Gemeno, César; Lutfallah, Adel F.; Haynes, Kenneth F.
Abstract : Sex pheromone quantity, blend ratio, and cross-attraction were studied in four populations of the black cutworm, Agrotis ipsilon (Hufnagel). Analysis of pheromone gland extracts showed that the three pheromone components of A. ipsilon, ( Z )-7-dodecenyl acetate (Z7-12: Ac), ( Z )-9-tetradecenyl acetate (Z9-14: Ac) and ( Z )-11-hexadecenyl acetate (Z11-16: Ac) were present in all four populations. On average, Z7-12: Ac was the most abundant component in the populations from Kentucky and Kansas, whereas in the Egyptian and French populations Z11-16: Ac was the most abundant component. All populations had a similar quantity of Z7-12: Ac. The population from Kentucky had significantly more Z9-14: Ac than the population from Kansas, and the other two populations had intermediate quantities of this component ( P < 0.05). The Egyptian population had significantly more Z11-16: Ac than the French population, which had significantly more than the populations from Kentucky and Kansas ( P < 0.05). Comparing Nearctic (Kentucky and Kansas) versus Palearctic (Egypt and France) populations showed significant differences in the quantity of Z11-16: Ac and in the ratio of Z11-16: Ac to Z7-12: Ac ( P < 0.01). Full-sib analysis revealed significant heritabilities in pheromone components and blend ratios in two of the populations. Cross-attraction between individuals from Kansas and from each of the other three populations was tested in paired experiments in a wind tunnel using live females as the source of pheromone. Males did not discriminate between females from their own population and females from the reference population. Thus, significant differences in pheromone blend among geographically distant populations of A. ipsilon did not prevent cross-attraction under laboratory conditions.